A multi-herb-combined remedy to overcome hyper-inflammatory response by reprogramming transcription factor profile and shaping monocyte subsets. (July 2021) - De, Gejing; Chen, Apeng; Zhao, Qinghe; Xie, Ran; Wang, Chaoxi; Li, Meng; Zhao, Haiyu; Gu, Xinru; McCarl, Lauren H.; Zhang, Fangbo; Cai, Weiyan; Yang, Miyi; et al.
Abstract: Traditional Chinese multi-herb-combined prescriptions usually show better performance than a single agent since a group of effective compounds interfere multiple disease-relevant targets simultaneously. Huang-Lian-Jie-Du decoction is a remedy made of four herbs that are widely used to treat oral ulcers, gingivitis, and periodontitis. However, the active ingredients and underlying mechanisms are not clear. To address these questions, we prepared a water extract solution of Huang-Lian-Jie-Du decoction (HLJDD), called it as WEH (Water Extract Solution of HLJDD), and used it to treat LPS-induced systemic inflammation in mice. We observed that WEH attenuated inﬂammatory responses including reducing production of cytokines, chemokines and interferons (IFNs), further attenuating emergency myelopoiesis, and preventing mice septic lethality. Upon LPS stimulation, mice pretreated with WEH increased circulating Ly6C - patrolling and splenic Ly6C + inflammatory monocytes. The acute myelopoiesis related transcriptional factor profile was rearranged by WEH. Mechanistically we confirmed that WEH interrupted LPS/TLR4/CD14 signaling-mediated downstream signaling pathways through its nine principal ingredients, which blocked LPS stimulated divergent signaling cascades, such as activation of NF-κB, p38 MAPK, and ERK1/2. We conclude that the old remedy blunts LPS-induced "danger" signal recognition and transduction process at multiple sites. To translate our findings into clinical applications, we refined the crude extract into a pure multicomponent drug by directly mixing these nine chemical entities, which completely reproduced the effect of protecting mice from lethal septic shock. Finally, we reduced a large number of compounds within a multi-herb water extract to seven-chemical combination that exhibited superior therapeutic efficacy compared with WEH. Graphical Abstract: ga1